The Painted Decoration of the Church of the Virgin at Sklavopoula, Crete - Albani, Jenny (Actual Problems of Theory and History of Art, 2016)
The Church of the Virgin at Sklavopoula in the Selino Province of the southwestern part of Crete is a single-nave church decorated with wall paintings of outstanding quality preserved nowadays in a poor condition. According to the painted dedicatory inscription, John, probably a high-ranking officer responsible for guarding the gate of the fort (presumably, the Castel Selino in the modern Paleochora), Alexius, his wife and his children, and Theodore were the donors of the erection and decoration of the church.The iconographic program of the wall paintings includes seven scenes from the Dodekaorton. The Christological cycle was enriched with one episode from the Passion cycle and two scenes from the Eothina cycle, which emphasize the idea of salvation. A restricted Mariological cycle, which consists of four scenes, and a portrait of the Virgin Hodegetria was also included in the program since the church is dedicated to the Virgin, who is the most important intercessor for the salvation of mankind. The eschatological character of the program is further accentuated by the large composition of the Last Judgment in the west part of the church in association with St. Nicholas, an intercessor par excellence, and Archangel Michael, the psychopompos and guardian of the Paradise’s gate.The wall paintings of the Church of the Virgin at Sklavopoula may be attributed to the work of two first class artists and at least one assistant. On stylistic grounds, they date to the last decade of the 14 th  century. Their refined style can be associated with a classicist stylistic trend of undoubtedly Constantinopolitan origin, which is represented on Crete by painted decorations of about 24 churches assigned to the period between 1380 and 1417.
Keywords: wall paintings; Venetian period; donor portrait; dedicatory inscription; Dodekaorton; Passion cycle; Eothina cycle; Last Judgment; classicist stylistic trend